Climate change and reproductive health - Nazli Hossain (Journal of the Pakistan Medical Association, 2024)
Climate change has become a global issue. World HealthOrganization (WHO) has estimated an increase of 250,000 deaths between 2030-2050, due to climate effect. ThoughPakistan does not contribute much to the cause of globalwarming, but suffers enormously due to climate change.The massive floods in 2022, in Sindh and Baluchistan provinces of the country caused tremendous destruction,and people are still unable to recover from these setbacks.The spectrum of climate change includes flood, drought,air pollution, wildfires, heat waves and increase in vectorbornediseases. All of this influence reproductive health. Iteffects both men and women. Pregnant women areincluded in the vulnerable group for these changes.Climate change has been identified as an important causeof maternal and perinatal mortality, as well as involves allaspects of obstetric outcomes. The resultingcomplications include preterm labour and delivery,decrease in gestational length, stillbirth, intrauterinedemise and a high rate of miscarriages. The effect ofclimate change on economy is also well established. With1°C rise in temperature, 12% decrease in global GDP isexpected. Continued...